The Agenda Setting of Corona: Analysis of the Corona Dissemination Impact on the Community - Muhammad Qadaruddin Abdullah; Nahrul Hayat; Abd. Rahman (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2020)
This study is based on news dissemination about the Corona Virus Disease 2019, COVID-19, as a global pandemic. The massive amount of coronavirus news dissemination provokes the audiences to behave inappropriately. This study uses the theory of agenda-setting, which elaborates on the process of forming opinion in national television media. After that, the theory of media exposure is used to analyze the impact of exposure to the COVID-19 dissemination on social media. The research method used is a combination of qualitative and quantitative methods, namely, survey and interview in social media that is on the WhatsApp group of students and lecturers in the Province of South Sulawesi. The results of this study; First, the process of forming an opinion by the public media has not done proportionally, the information dissemination of the coronavirus had covered the dissemination of other important cases, such as the legal and corruption issues. Second, the effect of the COVID-19 news dissemination on social media not only had an impact on people's health but also a multi-effect toward the economic, religious, and psychological condition. The multi-dimensional impacts are responsible for setting the exposure of COVID-19 news dissemination as the single issue that makes the diversion of opinion and other issues occurred, such as legal and corruption cases which are no longer being a public talk.